Secrets I keep - Thurgood, Mikaila Rae (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
My mother had many failings. Her inability to cook. Her inability to work. Her inability to love. But her two biggest failings...those were the ones that had the potential to ruin my entire life, to ruin my brother's life, to tear a family apart. More than anything, it was her inability to act. Claire is a young woman working in Johannesburg as a PA. She has few friends barring her au pair flatmate Beth and work colleague Marge. Her nights are spent trying to overcome the trauma of her past to find sexual fulfilment in a shallow world of one night stands. Whether she can set herself on a path towards a more normal life comes down to one crucial thing "“ forgiveness.
Keywords: South African fiction (English) -- 21st century; Creative writing (Higher education) -- Research -- South Africa; Creative writing -- Fiction; South African fiction (English) -- Study and teaching (Higher)